Developing Student Teachers' Sustainability Competence through Picturebooks - Malin Lidström Brock (CLELEjournal, 2024)
The first article details an endeavour to answer the call for all educators to promote sustainability. Brock's paper outlines a teacher education sequence in an English course at a Swedish university. The four activities illustrated aimed for sustainability competence through picturebooks.